Russian Political Blogs as Relevant Practice of Protest Communication : Systemic-Communicative Dimensions - M. V. Milovanova; E. V. Terentyeva (Научный диалог)
The article is devoted to the study of a collective-personal, subject-oriented measurement of Russian-speaking protest communication in the framework of a broad communicative approach. The material was the content of political blogs hosted on the livejournal platform, the platform of the Echo of Moscow information site, and individual domains. The heterogeneity of functions characteristic of political blogs is revealed in the article. The language tools representing these functions are characterized. Particular attention is paid to the discursive hybridity of political blogs, manifested in the inclusion in the Internet discourse of elements of political, business, legal, conversational, artistic discourse. The specifics of constructing a complex addressee (individual, collective, title) and complex addressee (mass, target) are described. Relevant communication strategies and tactics of the mass, individual addressee are disclosed. Discussion topics that initiate a protest reaction of the addressee were identified, among which finance and taxes, government and administration, elections, corruption, officials, healthcare, parties and politicians, and social issues dominate. The stages of discursive construction of the problem in political blogs are shown. The ways of forming and maintaining Internet mobilization in the protest practice under consideration, the features of mediation of politics and personality in the analyzed content are described. The results obtained contribute to further understanding of the forms of modern protest, the interconnection of technology, politics and the media sphere.